Manoel de Oliveira and the reconciliation between theatre and cinema: forms and resources for the audiovisual preservation of theatre in his films. - Ruiz-del-Olmo, Francisco Javier; Cantos-Ceballos, Antonio (Taylor & Francis, 2023)
The extensive, enigmatic, and singular work of the Portuguese filmmaker Manoel de Oliveira (1908-2015) has been analysed from many perspectives, emphasising the importance of literary adaptations and the historical and cultural contexts in which the main characters are situated, as well as the pictorial or visual references. This research, however focuses on ways of integrating and preserving theater within the language of film, particularly those produced in the 1970s and 1980s. This study selects and analyzes some of the characteristics and features of the theatrical forms identified in Manoel de Oliveira's films, and unravels them. These include the use of spaces and frames to denote narratives, the duality between the static and the dynamic, and the importance of the spoken word in his films.
https://openpolicyfinder.jisc.ac.uk/id/publication/11074
Keywords: Oliveira, Manoel de. 1908-201 - Crítica e interpretación; Portuguese cinema; Theatre; Intertextuality; Filmic language